2003
DOI: 10.1016/s0735-1097(03)00955-0
|View full text |Cite
|
Sign up to set email alerts
|

Competing autonomic mechanisms precedethe onset of postoperative atrial fibrillation

Abstract: In the period before the onset of postoperative AF, there are significant increases in HRV during a time when heart rate also increases. These novel findings are consistent with parasympathetic resurgence competing with increasing sympathetic activity as the triggering mechanism for postoperative AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(137 citation statements)
references
References 32 publications
6
125
0
6
Order By: Relevance
“…Coumel et al 53 in 1978 first reported that cardiac autonomic activities might predispose patients to develop paroxysmal atrial arrhythmias. Subsequent studies [54][55][56] with heart rate variability analysis indicate that, rather than being triggered by either vagal or sympathetic activity, the onset of AF can be associated with simultaneous discharge of both limbs, leading to an imbalance between these 2 arms of cardiac ANS. With implanted radiotransmitters, spontaneous simultaneous sympathetic (from LSG) and parasympathetic (from thoracic vagus nerve) nerve activity was observed to precede the onset of paroxysmal AF in ambulatory dogs with rapid atrial pacing ( Figure 3A) 48 and HF.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…Coumel et al 53 in 1978 first reported that cardiac autonomic activities might predispose patients to develop paroxysmal atrial arrhythmias. Subsequent studies [54][55][56] with heart rate variability analysis indicate that, rather than being triggered by either vagal or sympathetic activity, the onset of AF can be associated with simultaneous discharge of both limbs, leading to an imbalance between these 2 arms of cardiac ANS. With implanted radiotransmitters, spontaneous simultaneous sympathetic (from LSG) and parasympathetic (from thoracic vagus nerve) nerve activity was observed to precede the onset of paroxysmal AF in ambulatory dogs with rapid atrial pacing ( Figure 3A) 48 and HF.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…11 Neurotransmitters released by postganglionic axons of one limb can readily act on nerve terminals of the other, and activation of peripheral components of one elicits activity in the other (reciprocal activation and accentuated antagonism) 11,12 ; it is, thus, difficult to imagine isolated and independent adrenergic or vagal effects in complex arrhythmias, like AF. Supporting evidence for potential clinical implications of these notions comes from several experimental and clinical studies, indicating that a primary increase in adrenergic tone followed by a marked modulation toward vagal predominance precedes episodes of paroxysmal AF, 10,[13][14][15][16] both in patients with lone paroxysmal AF and in those with structural heart disease. 15 This knowledge, mainly formulated by studies conducted during the past decade, is important for potential therapeutic modalities aimed at modulation of the autonomic system: inhibition of the sympathetic limb can be expected (at least in principle) to have an effect not only in the small subset of AF patients with predominantly adrenergic AF but also in the majority of patients with paroxysmal AF.…”
Section: Discussionmentioning
confidence: 98%
“…Rapidly firing foci initiating paroxysmal AF arise most commonly from the atrial myocardial sleeves that extend into pulmonary veins. (11) Although the pulmonary veins are the most common sites for ectopic focal triggers, they can also arise SIGNA VITAE 2017; 13(2): [14][15][16][17][18][19] elsewhere, including the posterior LA (left atrium), ligament of Marshall, coronary sinus, venae cavae, septum, and appendages. Atrial myocardial fibers are oriented in disparate directions, and possess unique anatomical and electrophysiological features for their arrhythmogenic nature.…”
Section: Pathophysiology Of Afmentioning
confidence: 99%